2002
DOI: 10.1002/aoc.286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron on the degradation of triphenyltin by pyoverdins isolated from Pseudomonas chlororaphis

Abstract: The yellow compound pyoverdin was isolated from the bacteria Pseudomonas chlororaphis, isolated from mud in Japan. A study of the effects of iron, phosphorus, manganese and zinc on degradation of triphenyltin (TPT) by pyoverdin (20 mg) was carried out in distilled water (30 ml) containing 6 mg l À1 concentration of TPT at 20°C for 48 or 96 h. The organotins in water were analyzed by gas chromatograph±mass spectrometry in the selected ion mode. The degradation of TPT by pyoverdin decreased with increase of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The properties of pyoverdins are consistent with their role as siderophores with a strong affinity for ferric iron. 9 Yamaoka et al 6 found that degradation of TPT by pyoverdins was inhibited by iron in water. In conclusion, the results suggest that DBT and TPT was reacted with the iron chelate site on pyoverdins.…”
Section: Degradation Of Dbt By Pyoverdinsmentioning
confidence: 99%
“…The properties of pyoverdins are consistent with their role as siderophores with a strong affinity for ferric iron. 9 Yamaoka et al 6 found that degradation of TPT by pyoverdins was inhibited by iron in water. In conclusion, the results suggest that DBT and TPT was reacted with the iron chelate site on pyoverdins.…”
Section: Degradation Of Dbt By Pyoverdinsmentioning
confidence: 99%